2023
DOI: 10.1177/15248380231151690
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Parenting Programs in Preventing Abusive Head Trauma: A Systematic Review and Meta-Analysis

Abstract: Parenting programs are the most common intervention for preventing the lethal form of child maltreatment, abusive head trauma (AHT). However, certain results of the effects of these programs have not yet been compared across studies. A systematic review with meta-analysis is warranted to quantitively synthesize the available evidence to identify effective elements and strategies of the programs for preventing AHT. This review aims to estimate AHT preventive parenting programs’ pooled effect on the reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…16 Such prevention programmes could decrease visits to emergency rooms for crying and reduce the incidence of AHT in small samples but failed to demonstrate a significant impact in two state-wide replication trials. 1,23,24 A recently published systematic review and meta-analysis revealed only marginal improvements in parental response to persistent crying and low evidence that educational interventions increase walking away from the crying infant. 18 In summary, up to now, there is no clear evidence that AHT can be reduced by educational programmes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…16 Such prevention programmes could decrease visits to emergency rooms for crying and reduce the incidence of AHT in small samples but failed to demonstrate a significant impact in two state-wide replication trials. 1,23,24 A recently published systematic review and meta-analysis revealed only marginal improvements in parental response to persistent crying and low evidence that educational interventions increase walking away from the crying infant. 18 In summary, up to now, there is no clear evidence that AHT can be reduced by educational programmes.…”
Section: Discussionmentioning
confidence: 99%
“…18 In summary, up to now, there is no clear evidence that AHT can be reduced by educational programmes. 18,23 However, how the diagnosis of AHT was established in the prevention studies remains questionable. If AHT was concluded on the basis of certain medical findings and not on the basis of a witnessed or admitted event, there may be a risk of false-positive diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that these commonly used and recommended measures are older and the limitations noted are expected given how much the literature has evolved. A plethora of measures have been created in response for specific purposes, populations, and psychological IPV subtypes (see Alexander et al, 2022 and Lohmann et al, 2023 for systematic reviews).…”
Section: Examining the Content Validity Of The Measure Of Psychologic...mentioning
confidence: 99%